Safety and Efficacy of Anidulafungin for Fungal Infection in Patients With Liver Dysfunction or Multiorgan Failure. (12th November 2016) - Verma, Anita; Auzinger, Georg; Kantecki, Michal; Campling, James; Spurden, Dean; Percival, Fran; Heaton, Nigel
Abstract: Background: The objective of this study was to review our clinical experience on the safety and efficacy of anidulafungin, an echinocandin antifungal, in the treatment of invasive fungal infections (IFIs) in patients with moderate to severe abnormal liver function tests or multiorgan failure and IFI, in a large United Kingdom Liver Centre. Methods: The clinical records of the first 50 consecutive patients treated for IFI with anidulafungin between January 7, 2009 and March 2, 2011 were analyzed. Data were collected on demographics, underlying disease, disease characteristics, hematological and biochemical parameters, IFI, concomitant bacterial and viral infections, response to anidulafungin, and anidulafungin-related adverse events. Results: The patients' median age was 54.3 years (range, 19.6–75.9); 60% were male. Twenty-two (44%) patients were liver transplant recipients. Others had hepatopancreaticobiliary disease (n = 15, 30%) or chronic liver disease (n = 11, 22%). Invasive fungal infection (predominantly Candida spp) was proven in 36 (72%) patients, probable in 14 (28%). Of 46 evaluable patients, 35 (76%) had a favorable anidulafungin treatment outcome. Forty-nine (98%) had abnormal liver function tests (LFTs) pretreatment; 31 (62%) had ≥1 LFT raised to ≥2× baseline during anidulafungin treatment. Conclusions: In this highly specialized group of patients, anidulafungin treatment was efficacious and well tolerated by those with decompensated liver disease, multiorgan failure, and high-risk liver transplant with proven or probable IFI.